Investigation and analysis of executive risks in green buildings with AHP approach - Aref Taromian; Faezeh Taherkhani; Shadi Motamedi (مهندسی و مدیریت ساخت)
Widespread concerns about energy conservation, global warming, and the depletion of the planet's non-renewable resources have led to the development and expansion of green buildings, not only as a luxury and well-being, but also as an undeniable necessity for Conserve the life of the planet. Due to the importance of the issue on a global scale, many countries are determined to develop these buildings, but unfortunately in our country, due to some obstacles, the pace of progress in this area is very slow. In this study, an attempt has been made to identify the most important obstacles and risks against the implementation and expansion of green buildings in the country, and then prioritize them through hierarchical analysis based on distributional questionnaires between experts and specialists. These obstacles can be overcome. According to the results of the questionnaires, in the main criteria section, economic, technological, social, legal, political and environmental criteria, respectively, took the first to last priorities. In the sub-criteria section, high initial cost, low energy cost and people's resistance to change and maintenance costs of green building systems were the most important priorities, respectively. In the end, we have tried to provide solutions and suggestions in order to reduce these obstacles.